2017
DOI: 10.4995/var.2017.5932
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity through VR-based documentation of cultural heritage. A theoretical approach based on conservation and documentation practices

Abstract: Abstract:The visualization of 3D reconstructed artifacts often requires significant computing resources. The implementation of an object in a virtual reality (VR) application even necessitates the reduction of the polygonal mesh. Consequently, the communication and dissemination of "authentic" 3D reconstructions via immersive VR technologies has been a nearly impossible feat for many researchers. However, is the issue really computing resources, or is it rather the notion of authenticity in an "auratic" sense,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Specifically, the finding of the highly significant effect of authentic experience on cognitive response contributes to the literature, extending previous studies on the relation between authenticity and cognition (e.g., Kim, Bonn, and Lee 2017; Yung and Khoo-Lattimore 2019). Additionally, the strong relationship between authentic experience and affective response in this study theoretically demonstrates that VR tourism content is closely related to the emotional immersive experience and substantially extends the findings of previous studies (e.g., Dueholm and Smed 2014; Muñoz Morcillo et al 2017; Mura, Tavakoli, and Sharif 2017). The result of the significant effect of cognitive response on affective response elucidates the theoretical relation between cognition and affection, extending previous studies of virtual communities (Gupta and Kim 2007) and VR tourism (Tussyadiah et al 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, the finding of the highly significant effect of authentic experience on cognitive response contributes to the literature, extending previous studies on the relation between authenticity and cognition (e.g., Kim, Bonn, and Lee 2017; Yung and Khoo-Lattimore 2019). Additionally, the strong relationship between authentic experience and affective response in this study theoretically demonstrates that VR tourism content is closely related to the emotional immersive experience and substantially extends the findings of previous studies (e.g., Dueholm and Smed 2014; Muñoz Morcillo et al 2017; Mura, Tavakoli, and Sharif 2017). The result of the significant effect of cognitive response on affective response elucidates the theoretical relation between cognition and affection, extending previous studies of virtual communities (Gupta and Kim 2007) and VR tourism (Tussyadiah et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Virtual heritage is playful in its character, engaging in an authentic experience, which functions as a means for tourists to break free of the routines and constraints of everyday life (Dueholm and Smed 2014), which can lead to enjoyment. 3D-based digital cultural heritage suggests that a more pluralistic notion of authenticity is desirable for researching and understanding the changing conditions of both media art and archaeological cultural heritage (Muñoz Morcillo et al 2017), which could result in visitors' emotional involvement. Because perceptions of authenticity are activated by experiences that involve all of the senses, the visual dimension is important in the experience of authenticity (Mura, Tavakoli, and Sharif 2017) and may influence potential tourists' flow state.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Thus, while positive effects were found in both other preview styles (360° VR tour and static image website), such effects were stronger in the immersive VR preview. Therefore, building on previous studies that have found authentic experiences to result in immersion (Mura, Tavakoli, and Sharif 2017;Muñoz Morcillo et al 2017), this research outlines the authentic experience delivered in a highly interactive and immersive sensory VR headset preview provides an even greater illusion of transporting tourism consumers to the hotel and the feeling of presence in the virtual environment than in other preview styles. Accordingly, supporting previous conceptualizations, VR provides a more complete pictorial representation of a hotel and has the capability to enhance consumers' immersion in the experience through making information more realistic to the tourism consumer while also developing realistic expectations that are met following a stay at the hotel.…”
Section: Theoretical Implicationsmentioning
confidence: 90%
“…• Additions are identified as well as buildings constructive sequence and historical phases. Concept of Authenticity (ICOMOS, 1994;Stovel, 1995;Jones, 2009) is accordingly defined, taking into account plausible hypotheses verified through virtual reconstruction (Muñoz Morcillo, Schaaf, Schneider & Robertson-von Trotha, 2017), to set the theoretical background of future restorationconservation projects;…”
Section: Introductionmentioning
confidence: 99%